2012
DOI: 10.2166/nh.2012.217
|View full text |Cite
|
Sign up to set email alerts
|

WaterWorld: a self-parameterising, physically based model for application in data-poor but problem-rich environments globally

Abstract: This paper describes a spatiaiiy expiicit, physicaiiy based giobal modei for water baiance. Its i Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 23 publications
1
106
0
3
Order By: Relevance
“…Reservoirs are smaller in dry months as water levels recede, which partly explain the high proportion of small reservoirs in the validation dataset. Because drying patterns can also depend on reservoir depth and catchment size, we calculated the catchment area for each reservoir and confirmed that the distribution of our validation dataset was representative of the distribution of basin-wide reservoir catchment sizes using the WaterWorld [52] zones of interest tool.…”
Section: Validation Datasupporting
confidence: 52%
“…Reservoirs are smaller in dry months as water levels recede, which partly explain the high proportion of small reservoirs in the validation dataset. Because drying patterns can also depend on reservoir depth and catchment size, we calculated the catchment area for each reservoir and confirmed that the distribution of our validation dataset was representative of the distribution of basin-wide reservoir catchment sizes using the WaterWorld [52] zones of interest tool.…”
Section: Validation Datasupporting
confidence: 52%
“…For carbon in above-ground biomass, we identified the total area of different vegetation types in both the current and alternative state through consultation with local experts (DFO Harmon et al, (1986). The overall economic value of these carbon stocks and how it differed between states was estimated using a range of carbon values (see SI (Mulligan & Burke, 2005;Mulligan et al, 2010;Bruijnzeel et al, 2011;Mulligan, 2012 forest cover for the alternative state based on the stakeholder consultation as described above. In the absence of a spatial representation of this alternative land cover, these changes were applied uniformly across the site.…”
Section: Global Climate Change Mitigationmentioning
confidence: 99%
“…WorldClim has been extensively used for several studies such as the analysis of the impact of climate change on agriculture and adaptation strategies by using crop-climate simulation models [43,52], as well as spatially explicit and physically based global models for water balance [53].…”
Section: Climatic Datamentioning
confidence: 99%